Genotyping of human lice suggests multiple emergencies of body lice from local head louse populations. - Wenjun Li; Gabriel Ortiz; Pierre-Edouard Fournier; Gregory Gimenez; David L Reed; Barry Pittendrigh; Didier Raoult (Public Library of Science (PLoS), 2010)
BACKGROUND: Genetic analyses of human lice have shown that the current taxonomic classification of head lice (Pediculus humanus capitis) and body lice (Pediculus humanus humanus) does not reflect their phylogenetic organization. Three phylotypes of head lice A, B and C exist but body lice have been observed only in phylotype A. Head and body lice have different behaviours and only the latter have been involved in outbreaks of infectious diseases including epidemic typhus, trench fever and louse borne recurrent fever. Recent studies suggest that body lice arose several times from head louse populations. METHODS AND FINDINGS: By introducing a new genotyping technique, sequencing variable intergenic spacers which were selected from louse genomic sequence, we were able to evaluate the genotypic distribution of 207 human lice. Sequence variation of two intergenic spacers, S2 and S5, discriminated the 207 lice into 148 genotypes and sequence variation of another two intergenic spacers, PM1 and PM2, discriminated 174 lice into 77 genotypes. Concatenation of the four intergenic spacers discriminated a panel of 97 lice into 96 genotypes. These intergenic spacer sequence types were relatively specific geographically, and enabled us to identify two clusters in France, one cluster in Central Africa (where a large body louse outbreak has been observed) and one cluster in Russia. Interestingly, head and body lice were not genetically differentiated. CONCLUSIONS: We propose a hypothesis for the emergence of body lice, and suggest that humans with both low hygiene and head louse infestations provide an opportunity for head louse variants, able to ingest a larger blood meal (a required characteristic of body lice), to colonize clothing. If this hypothesis is ultimately supported, it would help to explain why poor human hygiene often coincides with outbreaks of body lice. Additionally, if head lice act as a reservoir for body lice, and that any social degradation in human populations may allow the formation of new populations of body lice, then head louse populations are potentially a greater threat to humans than previously assumed.